Estudo da transição entrópica do DNA induzida por intercalantes utilizando a técnica de Pinçamento Óptico e Espectroscopia de autocorrelação de intensidades - Maria Clara Goncalves Miranda Ferreira (2007)
At the present work measurements of persistence and contour length of DNA drug complexes were performed. The effects of two drugs that intercalates DNA molecule were studied: daunomycin and ethidium bromide. A systematic study of the effect of the drug concentration on the DNA persistence and contour length is presented. For this purpose, a system of optical tweezers and intensity autocorrelation spectroscopy were used. It was observed that the persistence length of DNA-drug complexes increases strongly as the drug concentration is raised up tosome critical value. However, for concentrations above this critical value, the persistence length decays abruptly and remains approximately constant for larger drug concentrations. This behavior suggests that a helix-coil transition might de occurring. The contour length of the molecules increases monotonically and saturates as drug concentration increases. The neighbor exclusion model fits the results found for the total drug concentration as a function of the relative increase of the contour length